Sudan wyimaginowany - refleksje na temat kształtowania się pojęcia Sudanu w okresie wpływów europejskich - Maciej Kurcz (Etnografia Polska, 2013)
Sudan, like many African countries, is a creation of the European imperialism. Not only the matter of borders is meant here, but complex processes of destruction and creation at the same time, which considerably affected what we understand today under the name of Sudan. The article explores the European ideas concerning Sudan, once the largest African country, which considerably contributed to the strengthening of Europe's hegemony in this territory during the period of colonialism and imperialism and today determine the phenomena of culture or political situation in this country. The reflections presented here have been formed by exploring the archives of colonial Sudan deposited at the Sudan Archive in Durham in North-East England.